Two occurrences of presumptive venous air embolism in a gelding during cystoscopy and perineal urethrotomy. (20th November 2015) - Gordon, E.; Schlipf, J. W.; Husby, K. A.; Tornquist, S. J.; Bildfell, R. J.; Semevolos, S. A.
Summary: A 14‐year‐old Arabian gelding presented for evaluation of macroscopic haematuria. Routine cystoscopy was performed under standing sedation during which the horse collapsed with apparent seizure activity. General anaesthesia was induced and the horse recovered neurologically normal. Four days later, during a perineal urethrotomy procedure, the horse experienced a similar collapse with seizure‐like activity. General anaesthesia was again induced and cystoscopy performed through the urethrotomy incision. A ventral bladder mass was visualised and sampled. Cytology confirmed a neoplastic process and the horse was subjected to euthanasia. Histopathology confirmed transitional cell carcinoma. Air embolism was the suspected cause of loss of consciousness and seizure activity in both instances.